2007
DOI: 10.1108/13620430710834413
|View full text |Cite
|
Sign up to set email alerts
|

Turnover intention and preparedness for change

Abstract: Purpose“Turnover intention” is defined as an employee's intention to voluntarily change jobs or companies. The purpose of this paper is to set “turnover intention” in relation to “preparedness for change”. The former relates to the change of jobs or companies, the latter to employees' willingness to change their current workplace. Both phenomena relate to employability, i.e. an employee's adaptability to changing internal (i.e. the current employer) and external labour market demands. The main aim of this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(40 citation statements)
references
References 50 publications
1
36
1
2
Order By: Relevance
“…The high rate of turnover intention among employees is widely understood as a damaging characteristic to be prevented in the work environment. Morrell et al (2001) and Schyns et al (2007) stated that despite a lot of literature on turnover, there is no widely recognized explanation of why workers want to leave corporations. However, Schyns et al, (2007) and Winterton (2004) maintained that it is closely linked to low work fulfillment, productivity and recruitment, and retention costs, along with the potential loss or lack of specific/implicit expertise and competencies of existing workers due to the real high turnover.…”
Section: Turnover Intentionmentioning
confidence: 99%
“…The high rate of turnover intention among employees is widely understood as a damaging characteristic to be prevented in the work environment. Morrell et al (2001) and Schyns et al (2007) stated that despite a lot of literature on turnover, there is no widely recognized explanation of why workers want to leave corporations. However, Schyns et al, (2007) and Winterton (2004) maintained that it is closely linked to low work fulfillment, productivity and recruitment, and retention costs, along with the potential loss or lack of specific/implicit expertise and competencies of existing workers due to the real high turnover.…”
Section: Turnover Intentionmentioning
confidence: 99%
“…Besides, few studies (e.g., Schyns, Torka, & Gossling, 2007;Vecchio & Norris, 1996) revealed that the link between LMX and employee turnover had been weak and unstable statistically. On the contrary, this study shows a very strong link between the two (-0.251, p = .002).…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…In most cases, turnover intention can happen either voluntarily where employee decides to leave the company by willingly (Schyns, Torka, & Gossling, 2007) or involuntarily, replacing an employee for a job position, mostly without the prior willingness of the employee (Bothma & Roodt, 2013;Price, 1977) According to (Ibrahim, Usman, & Bagudu, 2013), the rate of turnover varies from institutions to institutions. Sometimes employee turnover is a benefit to an organizations in a positive way.…”
Section: Turnover Intentionmentioning
confidence: 99%